FORECASTING ANALYSIS OF ZIS COLLECTION IN BANJAR REGENCY USING DOUBLE EXPONENTIAL SMOOTHING METHOD - Malihah, Lola; Ma'mun, Muhammad Yulian; Mahfuzah, Annisa; Karimah , Husna; Meilania, Gusti Tasya; Murliana, Mera (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
The purpose of this study is to observe forecasting zakat collection funds and other Islamic religious charity (ZIS) that the Banjar Regency Baznas collect from October 2021 to March 2022. The method used is the Double Exponential Smoothing method, and analyzed by using the parameters ð›¼ = 0,4 ð‘‘ð‘Žð‘› ð›¾ = 0,1. For this study, secondary data of Baznas Banjar Regency collection funds covering from January 2018 to September 2021 was obtained from its institution. The findings show that forecasting with this method resulted in ZIS collection will be increased monthly for the next six months. Therefore, the data will benefit Baznas Banjar Regency and other stakeholders in planning and evaluating the management of ZIS funds. Thus, policymakers can use it to improve public welfare and poverty alleviation in Banjar Regency.